Implementation of Healing Environment in A Beauty and Wellness Center (Case Study in Bandar Lampung City) - Kamila, Nabila Aqil (Journal of Engineering and Scientific Research, 2024)
The increasing interest in beauty and healthy lifestyles seems to have become a major need for Indonesian society. So it's not only women who take care of themselves, but now men also do the same thing. This of course needs to be balanced by providing beauty and health support facilities. Beauty and wellness center is an integrated beauty and health care center consisting of several facilities such as beauty clinics, salons, fitness and health centers. The method used in this research is a descriptive qualitative method, namely research on an object in real conditions using descriptive methods. Data processing is carried out by means of analysis to produce design concepts. Based on the analysis and design concept of the beauty and wellness center in Bandar Lampung City, it can be concluded that this building can facilitate beauty and health care in one integrated building. The application of the healing environment concept aims to provide a balance between humans, the environment and nature in the building so as to create a calm atmosphere and help restore the physical and mental health of building users.